2008
DOI: 10.1158/0008-5472.can-07-3105
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomic Profiling of Chronic Lymphocytic Leukemia Identifies Subtypes of Deletion 13q14

Abstract: Chronic lymphocytic leukemia (CLL) is a biologically heterogeneous illness with a variable clinical course. Loss of chromosomal material on chromosome 13 at cytoband 13q14 is the most frequent genetic abnormality in CLL, but the molecular aberrations underlying del13q14 in CLL remain incompletely characterized. We analyzed 171 CLL cases for loss of heterozygosity and subchromosomal copy loss on chromosome 13 in DNA from fluorescence-activated cell sorting-sorted CD19 + cells and paired buccal cells using the A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(184 citation statements)
references
References 50 publications
9
171
3
1
Order By: Relevance
“…35 Interestingly, in addition to miR-15/16, this region also contained DLEU7 gene (that was previously identified as a candidate tumor-suppressor gene at 13q14) located telometic to miR-15/16. 35, 36 We investigated whether DLEU7 can also function as a tumor suppressor and cooperate with miR-15/16, 37 as DLEU7 is the only protein-coding gene located within reported deleted region.…”
Section: Mir-15/16 Cooperates With Dleu7 In Cll Pathogenesismentioning
confidence: 95%
“…35 Interestingly, in addition to miR-15/16, this region also contained DLEU7 gene (that was previously identified as a candidate tumor-suppressor gene at 13q14) located telometic to miR-15/16. 35, 36 We investigated whether DLEU7 can also function as a tumor suppressor and cooperate with miR-15/16, 37 as DLEU7 is the only protein-coding gene located within reported deleted region.…”
Section: Mir-15/16 Cooperates With Dleu7 In Cll Pathogenesismentioning
confidence: 95%
“…This suggests that DLEU2 have specific function, beside MIR15A/16-1. In addition, the loss of other genetic elements in the vicinity of the human MDR may also participate to CLL pathogenesis and severity [118]. Subsequent works have further investigated the involvement of miRNAs in CLL, associating patterns of expression with clinical features [119].…”
Section: Noncoding Alterations: Mi-rnamentioning
confidence: 99%
“…Type II 13q deletions are defined by deletion of RB1, as described by Ouilette et al 17 and have previously been found to be enriched in patients who received treatment or had a higher clinical stage. 17 Therefore, 13q deletion types were assigned to our cases.…”
Section: Cll Patients Are Characterized By Considerable Genomic Hetermentioning
confidence: 99%
“…15,16 It has been proposed that 13q deletions could be categorized into two types; Type I deletions target a region including the MDR, whereas larger Type II deletions include the RB1 locus and were enriched in treated patients and those with higher Rai stage. 17 The significance of large 13q deletions and RB1 in particular, is further emphasized by their association with elevated genome complexity. 18 It is likely that the biological consequence of a unique deletion anatomy is complex, resulting in the disruption of multiple regulatory sequences.…”
Section: Introductionmentioning
confidence: 99%